تنافسية عواصم الاقتصاد الإسلامي: التمويل الإسلامي نموذجا - البشير، فضل عبدالكريم محمد Albashir, Fadl Abdulkarim Mohammed (المعهد الإسلامي للبحوث والتدريب, 2017)
يهدف هذا البحث إلى تحديد ملامح عاصمة الاقتصاد الإسلامي: التمويل الإسلامي نموذجا، في ضوء التنافس القائم حاليا بين أربع عواصم مختلفة هي: لندن، وكوالالمبور، ودبي، والمنامة، من خلال العرض والتحليل والدراسة لتوجه هذه العواصم الأربعة نحو الاقتصاد والتمويل الإسلامي؛ وإضافتها لهذا لقطاع إلى القطاعات الاقتصادية الأخرى في هذه الدول، في ضوء الأبعاد المختلفة التي أدخلها مفهوم التنافسية على صناعة الخدمات المالية الإسلامية؛ مما شكل واقعا متجددا يسعى نحو تطوير هذه الصناعة، يتناول البحث بالعرض والتحليل والمناقشة تنافسية التمويل الإسلامي في هذه العواصم الأربع، ويحلل مكوناته المتعددة؛ من حيث حجم الأصول المصرفية، والصكوك الإسلامية، والصناديق الاستثمارية، والتأمين التكافلي، والمؤسسات العلمية والعملية الفاعلة والداعمة لهذه الصناعة. كما يناقش البحث الدعم الحكومي الذي تقدمه حكومات هذه الدول، والمبادرات المختلفة التي تتبناها لجعل الاقتصاد والتمويل الإسلامي رافدا جديدا معززا لدور القطاعات الاقتصادية الأخرى في تحقيق النمو والتميز والابتكار وتطوير المجتمعات؛ في ظل الإقبال الكبير على منتجات الصناعة المالية الإسلامية. ويسعى البحث للوصول إلى نتائج تساهم في إبراز قدرات العواصم المتنافسة على قيادة الاقتصاد الإسلامي عبر استخدام مؤشر تطور التمويل الإسلامي في قطاعاته المختلفة الصادر عن مؤسسة تومسون رويترز، والمؤسسة الإسلامية لتنمية القطاع الخاص، في مجال التطور الكمي في التمويل الإسلامي والتعليم، والحوكمة، والمسؤولية الاجتماعية، والوعي والمعرفة بقطاع التمويل الإسلامي، للتمييز بين أفضل عواصم الاقتصاد الإسلامي.
This research aims to determine the features of Islamic Economics capitals and Islamic finance intermediation model in light of the competition exists between four capitals, London, Kuala Lumpur, Dubai, and Manama, through the presentation and analysis of their orientation towards Islamic economics and finance. In addition, these four capitals add this sector to the other economic sectors in the light of various dimensions underlying the concept of competitiveness of the Islamic financial services industry, which is considered as an endeavor towards the development of the industry. This paper addresses the presentation and analysis of competitive Islamic finance in these four capitals and analyze multiple components in terms of banking assets, Islamic instruments, investment funds, Takaful insurance, scientific and practical institutions that are active and supportive of the industry. In addition, it discusses the subsidies the governments of these countries offer and the various initiatives adopted to render Islamic economics and finance a new arm to enhance the role of other economic sectors in achieving growth, innovation and development of communities in the light of the great demand for Islamic financial industry products. This paper seeks to get to the results contribute to highlight the capabilities of competing capitals on the leadership of the Islamic economy through the use of some global competitiveness indicators Prepared by Thomson Reuters Foundation and the Islamic Corporation for the Development Private Sector (ICD), in field of quantitative development in Islamic finance, education, governance, social responsibility, awareness and knowledge to distinguish between the best capitals to leadership.
Keywords: الاقتصاد الإسلامي -- التمويل الإسلامي -- البنوك الإسلامية -- التأمين التكافلي